Beach Day by Rodger Bliss
May 2024
S M T W T F S
 1234
567891011
12131415161718
19202122232425
262728293031  

Three Positive Numbers

Three Positive Numbers
What three positive numbers give the same result when multiplied and added together?

Submit your Guess

 

 

 

You can use these HTML tags

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

8 guesses to Three Positive Numbers


    Warning: Use of undefined constant bfa_comments - assumed 'bfa_comments' (this will throw an Error in a future version of PHP) in /home/customer/www/riddledude.com/public_html/wp-content/themes/atahualpa/comments.php on line 132
  • Frank, you are today’s winner!
    1, 2, and 3.

  • brent

    Looks like the square root of 3 would also solve this riddle if it is used as all three values.
    root 3 x root 3 x root 3 = root 3 + root 3 + root 3

    I don’t know how to tell if there are other solutions (other than the one Frank gave) where three unique values solve the problem? Any ideas?

  • brent

    O.K. I’ve found a general solution (but my inability to enter math formulae on here is a bit frustrating, I’m happy to follow-up if there is interest.

    But for example,
    If you assume A = square root of (11.1)
    Which is approximately 3.331666

    Then this is true:
    A/10 + A + Ax10 = A/10 x A x Ax10
    or approximately
    0.3331666 + 3.331666 + 33.31666 = 0.3331666 x 3.331666 x 33.31666 = 36.98149

  • brent

    For some reason, this one has captured me!

    Another three positive numbers that add up to their product are:
    (Where B = square root of 3.5)
    B/2 + B + 2B = B/2 x B x 2B

    Or approximately:
    0.935414 + 1.870829 + 3.741657 = 0.935414 x 1.870829 x 3.741657 = 6.5479

  • brent

    Oh boy, it is much easier than I had been making it out to be.

    Given any two positive numbers: B & C you can find the 3rd (usually smaller) number to complete the equation:
    A + B + C = A x B x C

    using: A = (B + C) / (B x C – 1)

    Of course, B x C – 1 must not equal 0.

    I think I can get on with my life now…